Fizyoloji - Aykora, Damla; Şirinyıldız, Ferhat; Barutçu, Özlem; Öz, Mehmet; Köksal, Burcu; Birsen, İlknur and Gürel, Elif Ezgi and Gökdemir, Gül Şahika (Academician Publishing Book DOI Portal, 2024)
-